À propos du contrôle social de la politique énergétique - Constans, Louis (Les Cahiers de droit, 1983)
This paper attempts to clarify the basic issues underlying the discussion of citizens' participation in public decision-making on energy policy and projects. It questions the assumption that such participation is possible, and recalls that energy policy is at present, at least in the French context, an area of conflict between government and various interest groups. It warns of possible misunderstandings due to the lack of an agreed definition of participation. Three major points are made in this connection. The first is that the usual instruments of citizens' participation in decision-making (public inquiries, parliamentary debates, etc.) have, for a number of technical and institutional reasons, become largely irrelevant as regards energy matters — as indeed in several other areas of policy. The second is that decision-making on energy policy and projects really allows for very little freedom of choice on the part of decision-makers : such freedom rarely goes beyond the setting of time-frames for the achievement of goals imposed by circumstances. Finally, it is suggested that invocation of the ideals of democracy is unhelpful : what is realistically possible amounts only to a greater openness and objectivity in decision-making processes aimed at giving citizens, not an illusory power to decide themselves or to block decisions by policy-makers, but the capacity to forewarn the latter about public feelings on energy issues.